War, religion, and empire the transformation of international orders - Phillips, Andrew, 1977- (Cambridge ; New York : Cambridge University Press, 2011)
"What are international orders, how are they destroyed, and how can they be defended in the face of violent challenges? Advancing an innovative realist-constructivist account of international order, Andrew Phillips addresses each of these questions in War, Religion and Empire. Phillips argues that international orders rely equally on shared visions of the good and accepted practices of organized violence to cultivate cooperation and manage conflict between political communities. Considering medieval Christendom's collapse and the East Asian Sinosphere's destruction as primary cases, he further argues that international orders are destroyed as a result of legitimation crises punctuated by the disintegration of prevailing social imaginaries, the break-up of empires, and the rise of disruptive military innovations. He concludes by considering contemporary threats to world order, and the responses that must be taken in the coming decades if a broadly liberal international order is to survive"--
"International orders do not last forever. Throughout history, rulers have struggled to cultivate amity and contain enmity between different political communities. From ancient Rome down to the Sino-centric order that prevailed in East Asia as recently as the nineteenth century, the impulse for order was most often realised via the institution of empire. The rulers of the Greek city-states, their Renaissance counterparts, and the feuding kings of China's Period of Warring States alternatively secured order within the framework of sovereign state systems. The papal-imperial diarchy that prevailed in Christendom from the eleventh century to the early sixteenth century provides yet a third form of international order, which was neither imperial nor sovereign but rather heteronomous in its ordering principles"--
Introduction; Part I. Conceptual Framework: 1. What are international orders?; 2. Accounting for the transformation of international orders; Part II. The Historical Transformation of International Orders: 3. The origins, constitution and decay of Latin Christendom; 4. The collapse of Latin Christendom; 5. Anarchy without society: Europe after Christendom and before sovereignty; 6. The origins, constitution and decay of the sinosphere; 7. Heavenly kingdom, imperial nemesis: barbarians, martyrs and the collapse of the sinosphere; 8. Into the abyss: civilization, barbarism and the end of the sinosphere; 9. The great disorder and the birth of the East Asian sovereign state system; Part III. Contemporary Challenges and Future Trajectories of World Order: 10. The Jihadist terrorist challenge to the global state system; Conclusion.
Description based on print version record.
Keywords: Religion and international relations; Church history -- Middle Ages, 600-1500.; Christianity and politics -- History -- Middle Ages, 600-1500.; Islam and politics; International relations; Terrorism -- Religious aspects; Religion and politics; Electronic books; RELIGION / Christianity / General; BODY, MIND & SPIRIT / Gaia & Earth Energies